Active surveillance in favorable intermediate-risk prostate cancer patients: Predictors of deferred intervention and treatment choice - Sayyid, Rashid K.; Klotz, Laurence; Benton, John Z.; Ma, Merry; Woodruff, Phillip; Satkunasivam, Raj; Terris, Martha K.; Wallis, Christopher J.D.; Klaassen, Zachary (Canadian Urological Association Journal, 2021)
Introduction: Active surveillance (AS) is increasingly used for favorable intermediate-risk (FIR) prostate cancer (PCa). Our objective was to determine oncological and sociodemographic predictors of deferred definitive therapy and decision for radical prostatectomy (RP) vs. radiotherapy (RT). Methods: The Surveillance, Epidemiology, and End Results (SEER) Prostate with Watchful Waiting database was used to identify all FIR PCa diagnosed between 2010 and 2015 opting for AS for at least one year following diagnosis. We sought to determine predictors of treatment and treatment type using multivariable logistic regression. Results: A total of 20 334 patients were identified. An annual decrease in incident FIR patients managed initially with AS between 2010 (4061) and 2015 (2947) was noted (p for trend <0.001); 17 895 (88.0%) patients underwent deferred RP and/or RT. Patients with higher baseline cancer volume and clinical stage were significantly more likely to discontinue AS. Patients of higher socioeconomic status were more likely to undergo deferred therapy, with increased odds for RT over RP. African American patients had lower odds of undergoing definitive intervention (odds ratio 0.83, p=0.030) and were significantly more likely to opt for XRT. Oncological characteristics leading to FIR classification influenced treatment choice at the time of deferred intervention: RT was treatment of choice in 86.3% and 86.0% of Gleason group 2 and prostate-specific antigen 10–20 FIR patients, respectively; 96.1% of treated cT2b-c FIR patients opted for RP. Conclusions: Most FIR PCa patients initially managed with AS eventually undergo deferred definitive therapy, with choice of treatment significantly influenced by patients’ baseline oncological and sociodemographic characteristics.